Position and Effectiveness of Bupati Team for Accelerating Regional Development in Majene District - Ansharullah; Faradilla Rizal Putri; Elisabet Linda Allo Alex (Kirana Publisher (KNPub), 2023)
This study examines the positioning and effectiveness of the district development acceleration escort team in the Majene district. The type of research used in this writing is normative-empirical, where the method studies library material as well as legislative regulations, and the effectiveness that occurs in society. This research approach is a legislative approach and a conceptual approach. Both approaches are used in analyzing the position and effectiveness of the Bupati support team to accelerate regional development in the district of Majene. This research is carried out with the aim that the research is useful and in accordance with the intended purpose, the purpose of the research to know the position and effectiveness of TBUP3D.